Sistem Informasi Inventory Sparepart Maintenance Berbasis Web Menggunakan Agile Software Development Pada PT. Unilever Indonesia - Asep Arwan Sulaeman; Indri Lestari (DPPM Universitas Pelita Bangsa, 2025)
The rapid advancement of information technology has encouraged digital transformation in industrial sectors, including the Maintenance Department at PT Unilever Indonesia. The department faces recurring challenges in managing machine maintenance, particularly during equipment failures and spare part replacements, due to the absence of a centralized and integrated system. Inefficient inventory management has affected operational effectiveness and asset control. This study aims to develop a web-based spare part inventory and maintenance information system using the Agile Software Development method. The system includes modules for asset data management, location tracking, asset status monitoring, and maintenance scheduling and documentation. Blackbox Testing was conducted to evaluate system functionality and ensure it meets internal user requirements. Implementation and user evaluation results show that the system improves work efficiency by up to 40%, reduces data entry errors, and accelerates spare part requests and maintenance scheduling. Additionally, it provides structured and traceable historical data to support data-driven decision-making. Overall, the system is expected to strengthen asset control, enhance maintenance accuracy, and support digital transformation within the company.